Rule of law approach to alleviation of poverty: An analysis on human rights dimension of governance - Khanam, Taslima (IIUC Studies, 2020)
A society without rule of law is similar to a bowl having holes in it, so it leaks. Without plugging the leaks, putting more money in it makes no sense. Almost this claptrap is going in the form of poverty mitigation programs. Retorting the fact, this paper reflects that substantial poverty must be implied as formed by society itself and argues that lots of inhabitants of the world are deprived of the opportunity to get improved livings and live in dearth, as they are not within the shield of the rule of law. They may possibly be the citizens of nation state in which they live; nevertheless, their chattels and workings are vulnerable and far less rewarding than these are addressed. To address this unfairness, the paper provides a concise overview on the impact of rule of law as the basis for the people of opportunity and equity following the study of analytical approach with interdisciplinary aspect. Particular emphasis is to be found on human rights dimension of governance, and legal empowerment for the alleviation of poverty. IIUC Studies Vol.15(0) December 2018: 23-32